-13/7+3/5+-1/7
1/3-3/5+5/7-7/9+9/11-11/13+13/15+11/13-9/11+7/9-5/7+3/5-1/3
tính
a,7 5/11-(2 3/7 + 3 5/11)
b,(-3)/5. 5/7 + (-3)/5. 3/7+ (-3)/5. 6/7
c,1/3.4/5+1/3.6/5-4/3
d,5/9 . 7/13 + 5/9 . 13 - 5/9 . 3/13
a: =7+5/11-2-3/7-3-5/11
=2-3/7=11/7
b: =-3/5(5/7+3/7+6/7)
=-3/5*2=-6/5
c: =1/3(4/5+6/5)-4/3
=2/3-4/3=-2/3
d: =5/9(7/13+13-3/13)
=5/9*165/13=275/39
Tinh A
(3/7-3/13+3/37)/(5/7-5/13+5/37)+(1/2-1/3+1/4-1/5)/(7/5-7/4+7/3-7/2)
Thực hiện phép tính:
1,-4/7 + 2/3x -9/14
2,17/13 - ( 4/13 - 11 )
3, 8 2/7 - ( 3 4/9 + 4 2/7 )
5, ( 2/3 - 1 1/2): 4/3 + 1/2
6, -5/13 + 2/5 + -8/13 + 3/5 - 3/7
7, 6/5 x 3/7 + 6/5 : 7/10 + 6/5
\(1,-\dfrac{4}{7}+\dfrac{2}{3}\times\dfrac{-9}{14}\)
\(=\dfrac{-4}{7}+\dfrac{-18}{42}\)
\(=\dfrac{-4\times6}{7\times6}+\dfrac{-18}{42}\)
\(=\dfrac{-20}{42}+\dfrac{-18}{42}\)
\(=-\dfrac{38}{42}\)
\(=-\dfrac{19}{21}\)
\(2,\dfrac{17}{13}-\left(\dfrac{4}{13}-11\right)\)
\(=\dfrac{17}{13}-\dfrac{4}{13}+11\)
\(=\dfrac{13}{13}+11\)
\(=1+11\)
\(=12\)
\(3,8\dfrac{2}{7}-\left(3\dfrac{4}{9}+4\dfrac{2}{7}\right)\)
\(=\dfrac{58}{7}-\left(\dfrac{31}{9}+\dfrac{30}{7}\right)\)
\(=\dfrac{58}{7}-\dfrac{31}{9}-\dfrac{30}{7}\)
\(=\dfrac{58}{7}-\dfrac{30}{7}-\dfrac{31}{9}\)
\(=\dfrac{28}{7}-\dfrac{31}{9}\)
\(=\dfrac{28\times9}{7\times9}-\dfrac{31\times7}{9\times7}\)
\(=\dfrac{252}{63}-\dfrac{217}{63}\)
\(=\dfrac{35}{63}\)
\(=\dfrac{5}{9}\)
\(5,\left(\dfrac{2}{3}-1\dfrac{1}{2}\right):\dfrac{4}{3}+\dfrac{1}{2}\)
\(=\left(\dfrac{2}{3}-\dfrac{3}{2}\right):\dfrac{4}{3}+\dfrac{1}{2}\)
\(=\left(\dfrac{2\times2}{3\times2}-\dfrac{3\times3}{2\times3}\right):\dfrac{4}{3}+\dfrac{1}{2}\)
\(=\left(\dfrac{4}{6}-\dfrac{9}{6}\right):\dfrac{4}{3}+\dfrac{1}{2}\)
\(=\dfrac{-5}{6}:\dfrac{4}{3}+\dfrac{1}{2}\)
\(=\dfrac{-5}{6}\times\dfrac{3}{4}+\dfrac{1}{2}\)
\(=\dfrac{-15}{24}+\dfrac{1}{2}\)
\(=\dfrac{-15}{24}+\dfrac{1\times12}{2\times12}\)
\(=\dfrac{-15}{24}+\dfrac{12}{24}\)
\(=\dfrac{-3}{24}\)
\(=-\dfrac{1}{8}\)
\(6,\dfrac{-5}{13}+\dfrac{2}{5}+\dfrac{-8}{13}+\dfrac{3}{5}-\dfrac{3}{7}\)
\(=\left(\dfrac{-5}{13}+\dfrac{-8}{13}\right)+\left(\dfrac{2}{5}+\dfrac{3}{5}\right)-\dfrac{3}{7}\)
\(=\dfrac{-13}{13}+\dfrac{5}{5}-\dfrac{3}{7}\)
\(=-1+1-\dfrac{3}{7}\)
\(=-\dfrac{3}{7}\)
\(7,\dfrac{6}{5}\times\dfrac{3}{7}+\dfrac{6}{5}:\dfrac{7}{10}+\dfrac{6}{5}\)
\(=\dfrac{6}{5}\times\dfrac{3}{7}+\dfrac{6}{5}\times\dfrac{10}{7}+\dfrac{6}{5}\)
\(=\dfrac{6}{5}\times\left(\dfrac{3}{7}+\dfrac{10}{7}+1\right)\)
\(=\dfrac{6}{5}\times\left(\dfrac{3}{7}+\dfrac{10}{7}+\dfrac{1\times7}{1\times7}\right)\)
\(=\dfrac{6}{5}\times\left(\dfrac{3}{7}+\dfrac{10}{7}+\dfrac{7}{7}\right)\)
\(=\dfrac{6}{5}\times\dfrac{20}{7}\)
\(=\dfrac{120}{35}\)
\(=\dfrac{24}{7}\)
tính nhanh: 1/3-3/5+5/7-7/9+9/11-11/13+13/15+11/13-9/11+7/9-5/7+3/5-1/3
Tính
1. 6/5 - 1/4 + 4/5 - 3/4
2. 7/9 - 5/12 + 2/9 - 7/12
3. -4/15 + 5/13 - 11/15 + 8/13
4. 9/15 - 7/13 +6/15 - 6/13
5. 12/5 - 3/7 + 3/5 - 4/7
6. 6/5 - 1/4 + 4/5 - 3/4 + 1/2
7. 13/7 - 8/6 + 8/7 - 4/6 - 1/3
Bài 2: thực hiện phép tính bằng cách hợp lý
a. A=(1/2-7/13-1/3)+(-6/13+1/2+1và1/3)
b.B=0,75+2/5+(1/9-1và1/2+5/4)
c.(-5/9).3/11+(-13/18).3/11
d.(-2/3).3/11+(-16/9).3/11
e.(-1/4).(-2/13)-7/24.(-2/13)
f.(-1/27).3/7+(5/9).(-3/7)
g.(-1/5+3/7):2/11+(-4/5+4/7):2/11
`@` `\text {Ans}`
`\downarrow`
`a.`
`A=(1/2-7/13-1/3)+(-6/13+1/2+1 1/3)`
`= 1/2 - 7/13 - 1/3 - 6/13 + 1/2 + 1 1/3`
`= (1/2 + 1/2) + (-7/13 - 6/13) + (-1/3 + 1 1/3) `
`= 1 - 1 + 1`
`= 1`
`b.`
`B=0,75+2/5+(1/9-1 1/2+5/4)`
`= 3/4 + 2/5 + 1/9 - 3/2 + 5/4`
`= (3/4+5/4)+ 1/9 + 2/5 - 3/2`
`= 2 + 1/9 - 11/10`
`= 19/9 - 11/10`
`= 91/90`
`c.`
`(-5/9).3/11+(-13/18).3/11`
`= 3/11*[(-5/9) + (-13/18)]`
`= 3/11*(-23/18)`
`= -23/66`
`d.`
`(-2/3).3/11+(-16/9).3/11`
`= 3/11* [(-2/3) + (-16/9)]`
`= 3/11*(-22/9)`
`= -2/3`
`e.`
`(-1/4).(-2/13)-7/24.(-2/13)`
`= (-2/13)*(-1/4-7/24)`
`= (-2/13)*(-13/24)`
`= 1/12`
`f.`
`(-1/27).3/7+(5/9).(-3/7)`
`= 3/7*(-1/27 - 5/9)`
`= 3/7*(-16/27)`
`= -16/63`
`g.`
`(-1/5+3/7):2/11+(-4/5+4/7):2/11`
`=[(-1/5+3/7)+(-4/5+4/7)] \div 2/11`
`= (-1/5+3/7 - 4/5 + 4/7) \div 2/11`
`= [(-1/5-4/5)+(3/7+4/7)] \div 2/11`
`= (-1+1) \div 2/11`
`= 0 \div 2/11 = 0`
b, A=1/3-3/5+5/7+7/9+9/11-11/13+13/15-9/11+7/9-5/7+3/5-1/3
\(A=\dfrac{1}{3}-\dfrac{3}{5}+\dfrac{5}{7}+\dfrac{7}{9}+\dfrac{9}{11}-\dfrac{11}{13}+\dfrac{13}{15}-\dfrac{9}{11}-\dfrac{7}{9}-\dfrac{5}{7}+\dfrac{3}{5}-\dfrac{1}{3}\left(+\dfrac{7}{9}\rightarrow-\dfrac{7}{9}\right)\)
\(\Rightarrow A=\dfrac{1}{3}-\dfrac{1}{3}-\dfrac{3}{5}+\dfrac{3}{5}+\dfrac{5}{7}-\dfrac{5}{7}+\dfrac{7}{9}-\dfrac{7}{9}+\dfrac{9}{11}-\dfrac{9}{11}-\dfrac{11}{13}+\dfrac{13}{15}\)
\(\Rightarrow A=-\dfrac{11}{13}+\dfrac{13}{15}\)
\(\Rightarrow A=\dfrac{-11.15+13.13}{13.15}\)
\(\Rightarrow A=\dfrac{-165+169}{195}=\dfrac{4}{195}\)
1, ( -2/5 + 3/10 ) : ( 2/-5 + |-4/3 - 2| )
2, 12,5 . -5/7 + 9 3/4 - 1,5 . 5/7
3, -1/4 . -5/13 - 5/4 . -7/13 + 1/1,3
4, ( -3/4 + 5/13 ) : 2/7 - ( 2 1/4 + 8/13 ) : 2/7
5, ( 3 - 3/4 + 2/3 ) - ( 2 - 4/3 - 3/2 ) - ( 1 - 7/3 - 9/2 )
6, -1/3 - 8/35 + -2/9 - 1/135 z+ 4/5 + -4/9 + 3/7
thang nay rot vl
1; = ( -4/10 + 3/10 ) : ( -2/5 + 2/3 ) = -1/10 : ( -6/15 + 10/15 ) = -1/10 : 4/15 = -1/10 . 15/4 = -15/40 = -3/8
2; = 25/2 . -5/7 + 39/4 + -3/2 . 5/7 = -125/14 + 39/4 + -15/14 = ( -125/14 + -15/14 ) + 39/4 = -10 + 39/4 = -40/4 + 39/4 = -1/4
3; = 5/52 + 35/52 + 40/52 = 40/52 + 40/52 = 80/52 = 20/13
4; = ( -39/52 + 20/52 ) . 7/2 - ( 117/52 + 32/52 ) . 7/2 = -19/52 . 7/2 - 149/52 . 7/2 = ( -19/52 + -149/52 ) . 7/2 = -168/52 .7/2 = -147/13
5; = ( 36/12 + -9/12 + 8/12 ) - ( -12/6 + -8/6 + -9/6 ) - ( 6/6 - 14/6 - 27/6 ) = 35/12 + 10/12 + 70/12 = 115/12
6; = -1/3 + -8/35 +-2/9 + -1/135 +4/5 +-4/9 +3/7 = (-1/3 + -2/9 + -4/9 ) + ( -8/35 + 4/5 + 3/7 ) + -1/135 = ( -1/3 + -2/3 ) + ( -8/35 + 28/35 + 15/35 ) + -1/135 = -1 + 1 + -1/135 = -1/135
tui thay ban Huy dot do
1, ( -2/5 + 3/10 ) : ( 2/-5 + |-4/3 - 2| )
2, 12,5 . -5/7 + 9 3/4 - 1,5 . 5/7
3, -1/4 . -5/13 - 5/4 . -7/13 + 1/1,3
4, ( -3/4 + 5/13 ) : 2/7 - ( 2 1/4 + 8/13 ) : 2/7
5, ( 3 - 3/4 + 2/3 ) - ( 2 - 4/3 - 3/2 ) - ( 1 - 7/3 - 9/2 )
6, -1/3 - 8/35 + -2/9 - 1/135 z+ 4/5 + -4/9 + 3/7